Economic Benefits and Challenges: Funding Tertiary Education for Economic Development in Greece - Stergiou, Konstantinos; Anastasiou, Sofia; Filippidis, Konstantinos (Archives of Business Research, 2023)
It is often proposed that governments should devote resources toward tertiary education to the point where marginal social costs equal marginal social value. A critical challenge in evaluating the viability of financing higher education correlates with the difficulty of connecting educational inputs with output. The argument for investment in tertiary erudition hinges on technological advances and demographic change, whereby individuals require periodic retraining within the information age, and increasing labor productivity could reduce the effects of an aging population. The aim of the present work was to view the current system of funding tertiary education in Greece and review some evidence on the economic benefits of funding tertiary education in this Country. In spite of funding obstacles, empirical evidence indicates that graduates improve economic output and social cohesion. Prioritize funding policies for equitable access, and investigate optimal levels of taxpayer subsidy in future research. While allocative problems permeate the higher education sector within different countries, observational and empirical evidence illustrate that graduates improve economic productivity and increase the tax revenues. Overall, funding tertiary education promotes economic development in the global knowledge economy that is undergoing evolution. In addition to having direct effects on the quality of human capital, funding for postsecondary education also has indirect effects on research infrastructure, innovation and economic growth. Investments in higher education and research and development are essential for fostering economic growth, technological progress, and competitiveness.